Efektivitas Mindful Education dalam Meningkatkan Kesejahteraan Mental, Prestasi Akademik, dan Keterampilan Sosial Siswa - Suwandi; Putri, Riska; Koimah, Siti Mariyatul; Zahra, Nur Amalia; Putri, Mas Fierna Janvierna Lusie (Academy of Social Science and Global Citizenship Journal, 2024)
Quality education is not solely determined by academic performance but also by the mental and emotional well-being of students. One effective approach to improving such well-being is through mindfulness. This study aims to analyze the implementation of mindfulness in education, particularly in the Indonesian context, and its impact on students' mental health, academic performance, and social skills. Using a meta-analysis method, this research integrates findings from various empirical studies published between 2015 and 2024, focusing on the effectiveness of mindfulness-based programs. The results indicate that mindfulness significantly reduces anxiety (Cohen’s d = 0.78), improves focus, and enhances students’ social skills (Cohen’s d = 0.72), although its impact on academic performance is moderate (Cohen’s d = 0.54). These findings highlight the potential of mindfulness programs in fostering holistic education. However, challenges such as teacher training and cultural adaptation need to be addressed. This study recommends integrating mindfulness into Indonesia’s educational system to create a balanced, inclusive, and sustainable learning environment.